Correlation models of diffuse solar-radiation applied to the city of São Paulo, Brazil - Oliveira, A. P.; Escobedo, João Francisco [UNESP]; Machado, A. J.; Soares, J. (Elsevier B.V., 2002)
Measurements of global and diffuse solar-radiation, at the Earth's surface, carried out from May 1994 to June 1999 in São Paulo City, Brazil, were used to develop correlation models to estimate hourly, daily and monthly values of diffuse solar-radiation on horizontal surfaces. The polynomials derived by linear regression fitting were able to model satisfactorily the daily and monthly values of diffuse radiation. The comparison with models derived for other places demonstrates some differences related mainly to altitude effects. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: diffuse solar radiation; clearness index; correlation modelling; São Paulo City